Air Pollution—An Overlooked Risk Factor for Idiopathic Pulmonary Fibrosis - Majewski, Sebastian (J Clin Med, 2020)
Air pollution is a major environmental risk to health and a global public health concern. In 2016, according to the World Health Organization (WHO), ambient air pollution in cities and rural areas was estimated to cause 4.2 million premature deaths. It is estimated that around 91% of the world’s population lives in places where air pollution exceeds the limits recommended by the WHO. Sources of air pollution are multiple and context-specific. Air pollution exposures are established risk factors for development and adverse health outcomes in many respiratory diseases, including asthma, chronic obstructive pulmonary disease (COPD), or lung cancer. However, possible associations between air pollution and idiopathic pulmonary fibrosis (IPF) have not been adequately studied and air pollution seems to be an underrecognized risk factor for IPF. This narrative review describes potential mechanisms triggered by ambient air pollution and their possible roles in the initiation of the pathogenic process and adverse health effects in IPF. Additionally, we summarize the most current research evidence from the clinical studies supporting links between air pollution and IPF.